2016
DOI: 10.1177/2047487316670255
|View full text |Cite
|
Sign up to set email alerts
|

Screening for atrial fibrillation during influenza vaccinations by primary care nurses using a smartphone electrocardiograph (iECG): A feasibility study

Abstract: Background: People with unknown atrial fibrillation (AF), who are often asymptomatic, have a substantially increased risk of stroke. Although recommended in European guidelines, AF screening is not routinely performed. Screening at the time of influenza vaccination presents an ideal opportunity to detect AF in large numbers in a primary care medical setting, with an existing annual recall system for patients aged !65 years. Design: Cross-sectional pilot study of handheld smartphone electrocardiogram (iECG) scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
81
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 17 publications
(25 reference statements)
8
81
3
2
Order By: Relevance
“…Previous studies have found the AliveCor accessory to have a range of sensitivities and specificities from 95% to 100% and 94% to 99%. 15,[42][43][44][45] The outstanding research question that needs to be addressed before any form of AF screening is implemented is that of the treatment of asymptomatic AF captured through screening. Most randomized clinical trials (RCTs) that examined the effect of anticoagulation medication on stroke risk among patients with AF were conducted on individuals with an established diagnosis of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found the AliveCor accessory to have a range of sensitivities and specificities from 95% to 100% and 94% to 99%. 15,[42][43][44][45] The outstanding research question that needs to be addressed before any form of AF screening is implemented is that of the treatment of asymptomatic AF captured through screening. Most randomized clinical trials (RCTs) that examined the effect of anticoagulation medication on stroke risk among patients with AF were conducted on individuals with an established diagnosis of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed newly identified AF in 0.8% (8/973) of patients. 13 In another larger feasibility study conducted in Hong Kong, 13,122 patients underwent community screening using the Kardia Mobile device. The rate of previously undiagnosed AF was 0.8% (101/13122).…”
Section: Utility Of Smartphone Ecg Detection Of New Afmentioning
confidence: 99%
“…Patients themselves were accepting of the iECG device. A follow-up study investigating AF screening by nurses using an iECG device in a practice setting again highlighted practice-specific barriers that were mainly related to staff time and funding [40]. Another recent study surveyed the views of healthcare practitioners in inner-city GP surgeries in Nottingham, UK, to ascertain their readiness for future screening in AF [41].…”
Section: Operating Staffmentioning
confidence: 99%